P2-S1.17 Evaluating native STAND: a peer education curriculum for healthy decision-making for native youth. (10th July 2011) - de Ravello, L; Rushing, S C; Doshi, S; Smith, M U; Tulloch, S
Abstract : Background: American Indian/Alaska Native (AI/AN) youth are disproportionately affected by a myriad of health and social conditions. Compared to other US teens, AI/AN youth have higher rates of sexually transmitted infections, teen pregnancies, tobacco use, alcohol use, and substance use. Native STAND (Native Students Together Against Negative Decisions), a 29-session peer educator curriculum was developed to address a range of sexual and reproductive health topics, including important communication and peer education skills. It is the first peer educator curriculum for healthy decision making developed for AI/AN youth. Methods: Eighty students attending four Bureau of Indian Education (BIE) boarding schools were selected to be trained as peer educators. The curriculum was delivered by trained adult staff at each school and the sessions occurred over the course of the school year with each session approximately 90 min in length. A pre- and post-test using Computer Assisted Self-Interviewing (CASI) was administered to the participants. At the end of the program, focus groups with peer educators and school staff and key informant interviews with facilitators and school administration were conducted to identify programmatic strengths and weaknesses and inform final program revisions. Results: Overall, analysis of pre- and post-test CASI data showed students at all four schools experienced increases in talking to peers about sexual health; in STI/HIV prevention and reproductive health knowledge; in the intention to use condoms to avoid pregnancy and STIs; and in condom self-efficacy indices. Focus groups and key informant interviews revealed that facilitators and students felt they learnt a lot through the curriculum and enjoyed the program; they saw the program as a badly needed source of clear and honest information; and they voiced their desire to have the program continue. Conclusions: Native STAND was well-received at all four sites by students, facilitators, and school administrators. Almost everyone felt that no topics should be eliminated and that all the curriculum's activities were relevant and important to include to address the unique needs of Native youth. We will incorporate findings from the evaluation into the curriculum and make it widely available.